The Effect of the Problem-Based Learning Model Supported by the PARADITA Media on the Mathematical Problem-Solving Skills of Elementary School Students - Nada Savaira Raihana; Jennyta Caturiasari; Alfiana Nurussama (FKIP - Universitas Riau, 2026)
This study was motivated by students’ low mathematical problem-solving skills in elementary school mathematics classes. This study aims to analyze the effect of the Problem-Based Learning model supported by PARADITA media on students’ mathematical problem-solving skills. This study employs a quantitative approach, a quasi-experimental method, and a nonequivalent control group design. The sample consisted of 46 students. The experimental class and the control class each had 23 students. Data were collected through a mathematical problem-solving test and documentation. The results indicate that the Problem-Based Learning model supported by the PARADITA media affects students’ mathematical problem-solving skills. The effect of the Problem-Based Learning model, supported by the PARADITA media, reached 55.9%, whereas that of the Number Head Together cooperative learning model was only 23.2%. The N-Gain analysis for the class using the Problem-Based Learning model supported by PARADITA media fell into the high category with a value of 0.8579, while the class using the Number Head Together cooperative learning model achieved an N-Gain value of 0.5121, which falls into the moderate category. Thus, the Problem-Based Learning model supported by PARADITA media can be used as an alternative learning method to improve elementary school students’ mathematical problem-solving skills.